Modelling of a bio inspired tactile sensor mimicking the responses of human mechanoreceptors - Nor Syamimi Mohamad Sabri (School of Mechatronic Engineering, 2016)
The objectives of this study are as follows to propose a bio inspired tactile sensorequipped with tactile sensing elements covering both static and dynamic components of mechanoreceptors; to assess the feasibility of replicating the function of fast adapting (FA) and slow adapting (SA) receptors using piezoelectric and piezoresistive components respectively, by using FEA simulations software COMSOL Multiphysics v 5.1; to propose a unit of a bio inspired tactile sensor with a suitable ridge dimensions including the size of the proposed strain gauge and PVDF thin film. The tactile sensor was built in mimicking the human glabrous skin properties. The skin structure was also ridged to improve the efficiency of both static and dynamic force detection in normal and shear directions. The scopes of the study are to address the optimum ridge shape, the height of the modelled epidermal ridge and to identify the optimum sensor placement (the depth below the skin surface) of the modelled bio inspired tactile sensor. Also, seek to obtain the shape and size of modelled strain gauge as well as the best strain gauges orientation with ability to predict the component of force in x,y and z directions. Finally, to produce and verified the PVDF output.